2021
DOI: 10.25174/2582-2675/2021/111211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic stresses and mitigation strategy associated with their tolerance in wheat

Abstract: Global warming influences environmental factors which directly and indirectly affects agricultural crop production by exposing to several new biotic and abiotic stresses. The abiotic stresses like heat, drought, moisture, salinity and pre harvest sprouting stresses are most common whose effect became more severe due to climate change. Globally wheat is the most widely cultivated and used crops due to its economic and social values. Its production and productivity are highly vulnerable to these abiotic stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Under water-deficit conditions, using abscisic acid, uniconazole, brassinolide, and jasmonic acid exogenously increased plant productivity [117]. It has also been demonstrated that salinity stress was alleviated in crops due to the application of gibberellic acid, zeatin, and ethephon [138]. The application of salicylic acid exogenously enhanced pea growth traits and biomass under high temperatures [46].…”
Section: Plant Growth Regulators and Osmoprotectantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under water-deficit conditions, using abscisic acid, uniconazole, brassinolide, and jasmonic acid exogenously increased plant productivity [117]. It has also been demonstrated that salinity stress was alleviated in crops due to the application of gibberellic acid, zeatin, and ethephon [138]. The application of salicylic acid exogenously enhanced pea growth traits and biomass under high temperatures [46].…”
Section: Plant Growth Regulators and Osmoprotectantsmentioning
confidence: 99%
“…Saline soil is reclaimed using various strategies, such as leaching excess sodium, deep ploughing to mix calcareous subsoil into topsoil, and applying acidifying minerals like gypsum and pyrite. Leaching is an effective method that works well on saline soil [138]. The proper shading of a plant under extreme temperature conditions helps to protect and improve plant productivity.…”
Section: Cultural Practicesmentioning
confidence: 99%